A41 Does the effect of micro-environmental factors on the appeal for adults' transportation cycling vary across macro-environments? An experimental study using manipulating photographs. Issue 2 (June 2015) - Mertens, Lieze; Van Cauwenberg, Jelle; Ghekiere, Ariane; Van Holle, Veerle; De Bourdeaudhuij, Ilse; Deforche, Benedicte; Nasar, Jack; Van de Weghe, Nico; Van Dyck, Delfien
Abstract: Background: Micro-environmental factors, instead of macro-environmental factors (including walkability, access to shops/services/work, and urbanization), are easier to change in existing neighborhoods and thus more practical to target for environmental interventions. Unfortunately, relationships between transportation cycling and more changeable, micro-environmental factors are less consistent. Moreover, for interventions we need to know how well the findings can generalize to other macro-environments. This study aims to identify if the effect of micro-environmental factors (evenness of the cycle path, speed limitation and degree of separation) on the appeal for adults' transportation cycling depends on macro-environmental factors. Methods: Purposeful convenience sampling was used to recruit 389 middle-aged adults between 45 and 65 years. Participants completed a web-based questionnaire consisting of socio-demographic characteristics and a series of choice tasks with manipulated photographs using a choice based conjoint (CBC) method. Conjoint analysis was used to analyze the data. Results: Although several interaction effects between the micro-environmental factors and the macro-environmental factor were significant, the direction of the effects across the different macro-environments did not differ, only the magnitude of the effect. Moreover, the macro-environment was clearly less important than the micro-environmental factors regarding the appeal for transportation cycling. Our results suggest that the strength of the main effects of the micro-environmental factors are mainly independent of the macro-environment and that the ranking of the relative importance of the three micro-environmental factors is similar in each macro-environment. Conclusions: Findings obtained from this research could inform environmental interventions in real life settings to modify similar micro-environmental factors in different macro-environments.